A plant–pollinator metanetwork along a habitat fragmentation gradient - Librán-Embid, Felipe; Grass, Ingo; Emer, Carine [UNESP]; Ganuza, Cristina; Tscharntke, Teja (Wiley, 2021)
To understand how plant–pollinator interactions respond to habitat fragmentation, we need novel approaches that can capture properties that emerge at broad scales, where multiple communities engage in metanetworks. Here we studied plant–pollinator interactions over 2 years on 29 calcareous grassland fragments selected along independent gradients of habitat size and surrounding landscape diversity of cover types. We associated network centrality of plant–pollinator interactions and grassland fragments with their ecological and landscape traits, respectively. Interactions involving habitat specialist plants and large-bodied pollinators were the most central, implying that species with these traits form the metanetwork core. Large fragments embedded in landscapes with high land cover diversity exhibited the highest centrality; however, small fragments harboured many unique interactions not found on larger fragments. Intensively managed landscapes have reached a point in which all remaining fragments matter, meaning that losing any further areas may vanish unique interactions with unknown consequences for ecosystem functioning.
Keywords: calcareous grasslands; landscape ecology; mutualism; network theory; plant–pollinator interactions